THE MOST IMPORTANT CHARACTER OF KHUVAYDO'S WORK - Zaripova Dilfuza Baxtiyorovna (American Journals, 2023)
This article explores the poet of Huvaydo, a major representative of mysticism poetry, exploring the thematic wealth, linguistic nuances and emotional power that define his lyrical style. It concludes with reflections on the impact of Huvaydo's lyricism and suggestions for further research.
Keywords: Huvaydo, lyrics, thematic wealth, linguistic nuances, emotional strength, influences, inspirations, creative process.